THE ROLE OF THE CONTENTS OF THE TEXT USED IN ADVERTISEMENTS ON THE CONSUMER BEHAVIORS: ANALYSIS OF SEVERAL CURRENT ADVERTISING PRACTICES ON TELEVISION - Zekiye TAMER GENCER (Fırat University, 2019)
The cultural similarities occured with development about the commercial, social , economic and political relations between the countries all of the world are the result of the globalization concept. The similarity occured by both the intensity of consumption as well as the disappearance of the difference between fake and necessary needs and cultural affectation has been made the infrastructure of new world order. For the commercial institution, the datas of consumer provide to stay alive at all of every stage from improving a good product / service the pricing , from penetration to pruchasing. These datas, which is an important parameter of the commercial process , is one of the most important tools that provide the consumption at the end of advertising investment. Lest the advertising activities are compatible with the all of other marketing activities, as a requirement for integrated communication, recognition of the consumer closely is required. By works of branding, result of the increasing similar products in the market for the consumers and the advertising investments, building the consumers who are connected emotionally and loyalty is the basic target for the businesses. The advertising texts which need extremely serious investment to reach the masses have the contents which create big groups of consumers and this constitutes the necessary infrastructure for this creation. In this study selected 5 television advertisings were analyzed by content analysis and consumption motivation provided on consumers was examined. The parameters used in the ad text , and the contents analyzed.for the creation of purchasing trends and motivation. These advertisements had been selected among the companies that invest frequently in tv channels recently.